2019
DOI: 10.1007/s12055-019-00868-1
|View full text |Cite
|
Sign up to set email alerts
|

Secondary infection of chylothorax with Serratia marcescens: a rare scenario post-cardiac surgery

Abstract: Infection of chylothorax is considered rare because chyle is inherently bacteriostatic. We report a case of an infected chylothorax occurring in a post-cardiac surgery patient caused by Serratia marcescens. Once considered a harmless saprophyte, Serratia marcescens is now recognized as an important opportunistic pathogen causing healthcare-associated infection with a propensity for antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Furthermore, although it has been indicated that the coexistence of empyema and chylothorax is rare because of the bacteriostatic nature of chyle, several reports have described cases of infected chylothorax [ 18 , 19 ]. In such cases, it was speculated that the loss of activated lymphocytes in chyle [ 20 ], hepatic hydrothorax [ 5 ], or concomitant immunosuppressive therapy [ 21 ] caused immunodeficiency. It has been reported that CC increases the risk of secondary immunodeficiency caused by lymphopenia or loss of immunoglobulins and various antibodies which may cause infectious chylothorax [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although it has been indicated that the coexistence of empyema and chylothorax is rare because of the bacteriostatic nature of chyle, several reports have described cases of infected chylothorax [ 18 , 19 ]. In such cases, it was speculated that the loss of activated lymphocytes in chyle [ 20 ], hepatic hydrothorax [ 5 ], or concomitant immunosuppressive therapy [ 21 ] caused immunodeficiency. It has been reported that CC increases the risk of secondary immunodeficiency caused by lymphopenia or loss of immunoglobulins and various antibodies which may cause infectious chylothorax [ 8 ].…”
Section: Discussionmentioning
confidence: 99%